The impact of introducing Electronic Fiscal Device (EFD) system in revenue collection in Tanzania - Nzota, Erasto (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Master of Business Administration in Corporate Management(MBA-CM) of Mzumbe University.